Where biomedicalisation and magic meet: Therapeutic innovations of elite sports injury in British professional football and cycling - Faulkner, A.; McNamee, M.; Coveney, C.; Gabe, J. (Social Science & Medicine, 2017)
Injury is a conspicuous feature of the practice and public spectacle of contemporary elite sports. The paper argues that the `biomedicalisation` thesis (medico-industrial nexus, techno-scientific drivers, medical optimisation, biologisation, the rise of evidence and health surveillance) goes some way to capturing the use in elite sports injury of some highly specialised mainstream therapies and some highly maverick biological therapies, which are described. Nevertheless, these main strands of biomedicalisation do not capture the full range of these phenomena in the contexts of sports medicine and athletes' practices in accessing innovative, controversial therapies. Drawing on multi-method qualitative research on top-level professional football and cycling in the UK, 2014-2016, we argue that concepts of `magic` and faith-based healing, mediated by notions of networking behaviour and referral systems, furnish a fuller explanation. We touch on the concept of `medical pluralism`, concluding that this should be revised in order to take account of belief-based access to innovative bio-therapies amongst elite sportspeople and organisations.